Construction and validation of an interprofessional simulated scenario for the identification and management of sepsis - Michèle da Silva Borges; Taiciana Chagas Camacho; Ana Luísa Petersen Cogo (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: Build and validate a realistic interprofessional simulation scenario for the identification and management of sepsis by doctors and nurses. Method: Methodological study developed in 2021, in two stages: construction of the guide and content validation by expert judges; and development of the simulation and validation of the scenario by doctors and nurses. 15 specialists participated in the research in the first stage and eight care professionals in the second stage. 0.8 was adopted as a parameter for the Content Validation Index (CVI). Results: The scenario guide addressed nosocomial sepsis with an abdominal focus in an adult patient and its validation obtained a total CVI of 0.97. All areas evaluated in the simulation scenario obtained agreement indices greater than 0.8. Conclusion: The construction and validation of the guide allowed the elaboration of guiding material for the development of an interprofessional simulated scenario, whose execution and validation process demonstrated its suitability in approaching the identification and management of sepsis by doctors and nurses. It is recommended to carry out future research evaluating its applicability to other situational contexts.